Wisata Alam Taman Nasional Gunung Halimun Salak: Solusi Kepentingan Ekologi dan Ekonomi - Meti Ekayani; . Nuva; Rizqiyyah Yasmin; Fernando Sinaga; La Ode M. Maaruf (Institut Pertanian Bogor, 2014)
The extended of Gunung Halimun Salak National Park (TNGHS) coverage area pose a conflict of interest which is trade-off between the interests of the TNGHS main functions as conservation areas (ecological interests) and interests of local people who use the forest for economic needs. One of the intangible environmental services of TNGHS is natural tourism in the used zone which can be a win-win solution alternative to the trade off of conservation and economic interests in conservation area. Natural tourism in national parks is a payments for ecosystem services (PES) scheme that will provide added value, both conservation and economic benefits as non-exploited activity that will not endanger the national parks preservation. Therefore, in this study, how the natural tourism activities in TNGHS can support conservation and local economic improvement is examined. The high economic value of tourism and economic impact i.e. multiplier effect and job opportunity demonstrate that natural tourism in TNGHS as environmental services is very important. Natural resources and the beauty of nature in TNGHS should be preserved to keep the sustainability of natural tourism, because without the conservation of natural resource thus will be no natural tourism, which means there will be no economic benefit to the community.